Management of tertiary institutions in small states : final report (UNESCO ParisFR, 1997)
Examines issues and concerns in the management of tertiary institutions in small states. Seeks to identify management models that can be used for effective management of these institutions. Identifies strategies for dealing with issues such as strategic planning, financing, accreditation and quality control. Recommends ways of strengthening institutions and enhancing the provision of tertiary education through regional and international cooperation.
DC